Pengaruh pemberian active isolated stretching (AIS) dan plyometric terhadap eksplosive power standing long jump ditinjau dari molekuler - Raminda, Santri; Kurniawan, Ryanda Masri; Aliun, Fatimah Wahab (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Flexibility is an important component of daily activities.1 Flexibility is the mobility of joints and muscle elasticity that allows for maximum joint movement in various positions. Many methods and techniques can be used for stretching, including active isolated stretching. There are several ways to efficiently train standing jump ability, one of which is through plyometric training. Purpose: To examine the effect of plyometric training on explosive power in standing long jumps from a molecular perspective. Method: A quasi-experimental study with a pretest-posttest two-group design. The study used a box jump to assess explosive power in the long jump. Twenty-two participants were divided into a control and a treatment group, and their jump distance was then assessed using a tape measure. The control group received Active Isolated Stretching (AIS), while the treatment group received Active Isolated Stretching (AIS) and additional plyometric training with box jumps. Results: Adolescent respondents in the treatment group experienced significant changes compared to those in the control group, with p-values ​​of 0.001 and 0.000 (<0.05). Conclusion: Active isolated stretching (AIS) and plyometric training significantly improved explosive power in the standing long jump in both the treatment and control groups. Keywords: Active Isolated Stretching (AIS); Box Jump; Plyometric; Standing long jump. Pendahuluan: Fleksibilitas merupakan komponen yang penting dalam beraktivitas sehari-hari. Fleksibilitas merupakan mobilitas sendi dan elastisitas otot yang dapat menjangkau maksimum gerakan sendi dari berbagai posisi. Banyak metode maupun teknik yang dapat digunakan untuk melakukan stretching, diantaranya active isolated stretching. Terdapat beberapa cara melatih kemampuan standing jump secara efisien salah satunya melalui latihan plyometric. Tujuan: Untuk melihat pengaruh pemberian latihan plyometric terhadap eksplosive power standing long jump yang ditinjau dari molekuler. Metode: Penelitian quasi experimental dengan pretest-posttest two group design. Penelitian dilakukan menggunakan box jump, terhadap daya ledak lompat jauh. Sebanyak 22 responden dikelompokkan ke dalam kelompok kontrol dan juga perlakuan yang kemudian dinilai dengan menggunakan meteran untuk mengukur jauh lompatan. Kelompok kontrol diberikan intervensi Active Isolated Stretching (AIS) dan kelompok perlakuan diberikan Active Isolated Stretching (AIS) dan diberikan tambahan latihan plyometric dengan box jump. Hasil: Responden yang merupakan remaja di kelompok perlakuan mengalami perubahan yang signifikan dibandingkan dengan remaja di kelompok kontrol dengan nilai p sebesar 0.001 dan 0.000 (<0.05). Simpulan: Terdapat pengaruh pemberian latihan active isolated stretching (AIS) dan plyometric terhadap eksplosive power standing long jump pada kelompok perlakuan dan kelompok kontrol. Kata kunci: Active Isolated Stretching (AIS); Box Jump; Plyometric; Standing long jump.